HIV Infection and Antiretroviral Therapy Impair Liver Function in People Living with HIV: Systematic Review and Meta-Analysis - Kay-Lee E. Strauss; Wendy N. Phoswa; Sidney Hanser; Kabelo Mokgalaboni (Pharmaceuticals)
Background: The use of antiretroviral therapy (ART) has improved the lives of people living with HIV (PLWH). However, its use is associated with secondary complications, notably hepatotoxicity. This systematic review and meta-analysis assess the effects of HIV infection and ART on liver function in PLWH. Method: A comprehensive literature search was performed in PubMed, Scopus, and Google Scholar from inception to 12 February 2025. Studies analyzing liver enzymes such as aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP) in PLWH undergoing ART, those who are ART-naïve, and HIV-negative individuals were considered. Data analysis was performed using a meta-analysis web tool, and the results were reported as standardized mean differences (SMDs) and 95% confidence intervals (CIs). Results: Twenty-six studies were included in the meta-analysis. The findings showed an increase in AST, SMD = 1.85 (0.93 to 2.78, p < 0.0001, I2 = 93.8%), and ALT, SMD = 2.65 (1.25 to 4.04, p = 0.0002, I2 = 97.8%) in PLWH who were naïve compared with those who were HIV negative. Additionally, there was a pronounced elevation in AST, SMD = 1.49 (0.48 to 2.50, p = 0.0038, I2 = 98%); ALT, SMD = 2.30 (1.14 to 3.45, p < 0.0001, I2 = 98%); and ALP, SMD = 1.40 (0.55 to 2.26, p < 0.01, I2 = 97%) in PLWH exposed to ART compared with HIV-negative individuals. However, there was no significant difference in ALP, SMD = 0.53 (–0.92 to 1.98, p = 0.4726, I2 = 98%) between PLWH who were ART-naïve and HIV-negative individuals. Conclusions: The results show that HIV infection and ART administration are associated with elevated liver function test enzymes, suggesting that each may contribute to liver dysfunction among PLWH. These results highlight the dual risk posed by HIV infection and ART exposure.